Clinical, cytogenetic and toxicological studies in rural workers exposed to pesticides in Botucatu, São Paulo, Brazil - Bréga Salete Marcia; Vassilieff Igor; Almeida Alaor; Mercadante Amauri; Bissacot Denise; Cury Paulo R.; Freire-Maia Dertia V. (Cadernos de Saúde Pública, 1998)
Pesticides can cause gene mutations and chromosomal aberrations in exposed individuals. We have investigated 24 workers exposed to pesticides. Clinical examinations and cytogenetic and toxicological tests were performed. Ten non-exposed individuals were used as controls. Toxicological dosages of copper, zinc and manganese (metals found in some pesticides), hepatic enzyme dosage (GOT, GPT, AR) and acetylcholinesterase activity were performed in 16 workers and 8 controls. In the exposed workers, the most relevant clinical symptoms were poor digestion with fullness sensation after meals, irritated eyes, headache and fasciculations. The exposed group showed significantly lower manganese dosage and acetylcholinesterase activity, and significantly higher levels of alkaline phosphatase. Cytogenetic studies showed significantly higher chromosomal aberrations in the exposed group compared to the control group. Although the workers used protection against the pesticide's fog, the results revealed that the workers were contaminated with the pesticides. Therefore, the cytogenetic, toxicological studies with clinical examination are necessary for monitoring workers who are exposed to pesticides in any situation.